Chapter Social mobility in the towns and countryside of Late Medieval Crown of Aragon (c. 1300- c. 1550): sources and methodological approaches - Reixach Sala, Albert; Viciano, Pau (Firenze University Press, 2025)
This chapter deals with the sources and methodologies available to study dynamics of social mobility in Late Medieval Crown of Aragon. We discuss the strengths and limitations of three different kind of sources: fiscal registers, municipal records and notarial sources (wills, probate inventories and wills). Secondly, we present four case studies based on the cities of Girona and Majorca, as well as the small towns of Sant Mateu and Castelló de la Plana (both in northern kingdom of Valencia). In Girona we trace family names through local tax registers combined with an approach centered on lists of municipal offices. We compare the latter approach with another on Palma (Majorca). Finally, we seek to detect changes in socioeconomic status through the minimum threshold of income fixed in general tax records in Sant Mateu, along with the evolution of families recorded in local wealth registers in Castelló.